Metode menjaga kualitas hafalan bagi penghafal al-qur’an - Bachraisy, Muhammad Badiul (Maliki Interdisciplinary Journal, 2025)
This study highlights the urgency of maintaining the quality of Qur’anic memorization in tahfizh education, as success is not merely measured by the number of verses memorized but also by the accuracy of recitation, fluency, comprehension of meaning, and the durability of memorization over time. Although many students are able to memorize large portions of the Qur’an, the quality of their memorization often falls short due to insufficient repetition, inappropriate methods, and the pressure to prioritize quantity over precision. The purpose of this research is to identify effective methods for developing strong and accurate memorization by reviewing approaches such as talaqqi, muraja’ah, sima’an, and mudarosah as discussed in the literature and previous studies. This study employs a library research method, analyzing sources related to tahfizh and strategies for improving memorization quality. The findings reveal that structured muraja’ah routines, direct guidance through talaqqi, group evaluations, and strong internal motivation play a significant role in ensuring that memorization remains solid and long-lasting. The combination of these strategies has been proven to enhance accuracy, fluency, and retention. Therefore, this research emphasizes that the tahfizh process must balance the addition of new memorization with the maintenance of previously learned portions to produce memorization that is correct, strong, and sustainable, while also providing both spiritual and academic benefits for the learners.